(untitled) (Journal of Asian Development Studies, 2025)
This paper critically examines the ongoing process of gentrification in Lahore’s Walled City, situating it within broader debates on access to urban space and state-driven heritage conservation. This process has proven contentious, as redevelopment has been selective and arbitrary: areas are prioritised based on donor funding and perceived economic potential, while community voices and interests are often excluded. This phenomenon raises concerns that gentrification is transforming the city’s heritage into an arena of power and exclusion. Methodologically, the study combines secondary literature with primary qualitative research. A review of global scholarship maps key debates on the social, economic, and political impacts of gentrification. At the same time, semi-structured interviews and interpretive analysis of community narratives reveal tensions between official redevelopment discourse and residents’ lived realities. The findings suggest a top-down, exclusionary model of development, advanced by state authorities, which is framed as an effort to harness the area’s tourism-driven economic potential. Although mass displacement has not occurred, residents report feelings of alienation and restricted access, citing the proliferation of upscale commercial development, rising living costs, and tighter state regulation of business activity. The paper argues that gentrification in the Walled City extends beyond physical redevelopment, representing a struggle over belonging, cultural representation, and power. It shows how a donor-funded, bureaucratically driven process privileges certain actors while marginalising others, underscoring the urgent need to balance heritage conservation and urban development with social inclusivity in urban policy.